2004
DOI: 10.1074/jbc.m311017200
|View full text |Cite
|
Sign up to set email alerts
|

Familial Parkinson's Disease-associated L166P Mutation Disrupts DJ-1 Protein Folding and Function

Abstract: Mutations in DJ-1, a protein of unknown function, were recently identified as the cause for an autosomal recessive, early onset form of familial Parkinson's disease. Here we report that DJ-1 is a dimeric protein that exhibits protease activity but no chaperone activity. The protease activity was abolished by mutation of Cys-106 to Ala, suggesting that DJ-1 functions as a cysteine protease. Our studies revealed that the Parkinson's disease-linked L166P mutation impaired the intrinsic folding propensity of DJ-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
282
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 259 publications
(306 citation statements)
references
References 54 publications
(84 reference statements)
21
282
2
Order By: Relevance
“…Immunofluorescence Confocal Microscopy-Cells were fixed in 4% paraformaldehyde, stained with appropriate primary and secondary antibodies, and processed for indirect immunofluorescence microscopy as described previously (16,35,(41)(42)(43). Analysis and acquisition were performed using a Zeiss LSM 510 confocal laser-scanning microscope.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunofluorescence Confocal Microscopy-Cells were fixed in 4% paraformaldehyde, stained with appropriate primary and secondary antibodies, and processed for indirect immunofluorescence microscopy as described previously (16,35,(41)(42)(43). Analysis and acquisition were performed using a Zeiss LSM 510 confocal laser-scanning microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Cell lysates were prepared from transfected cells and immunoprecipitations were carried out as described previously (16,35,(41)(42)(43) using the indicated antibodies, followed by the recovery of immunocomplexes with protein G-Sepharose beads (Upstate). For co-immunoprecipitations of endogenous proteins, the Seize Primary Mammalian Immunoprecipitation Kit (Pierce) was used according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…DJ-1, a conserved protein with 189 amino acids, is ubiquitously expressed but is found at particularly high levels in the testis, brain and kidney (Olzmann et al, 2004). DJ-1 was originally identified as a novel oncogene product in conjunction with the small G-protein Ras in NIH3T3 cells (Nagakubo et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of DJ-1 has a neuronal cytoprotective effect against oxidative stress (14,15), whereas DJ-1 deficiency leads to increased oxidative stress-induced cell death, both in culture and in animal models (16,17). It has also been shown that the pathogenic L166P mutation impairs the neuronal cytoprotective function of DJ-1 by jeopardizing dimer formation and protein stability (18).…”
mentioning
confidence: 99%